Open window into professional learning: Post-qualifying learning among Japanese social workers. (November 2019) - Asano, Takahiro
This study examined how Japanese social workers understood learning experiences and continued to learn as professionals in their working context with qualitative methods: interviews and observations. They saw their learning as something about changes in their understanding in varying ways. Although those perspective changes in learning varied widely depending on their learning situation, three components of professional learning have been identified: Experience; Opportunity; and Reflection. These three components are not entirely distinct from each other, but inextricably interwoven. The findings in the study indicate that there is a significant gap between what the social workers value in learning and what is expected from professional communities including their organisations, professional associations, and universities in today's uncertain working environments, where 'control and standardisation' are increasingly emphasised within the evidence-based practice movement. In the gap, the voices of social workers have been underrepresented in the discourse of professional development—which tends to centre on the form of formal learning—in their professional communities. To share the awareness of diverse and complex learning as experienced by social workers themselves can be a first step in making a difference to professional learning in the context of Japanese social work.